Introduction to electronic circuit design. - Ghausi, Mohammed Shuaib, ....-; Spencer, Richard R., ....- (Upper Saddle River : Prentice Hall, 2003)
A basic understanding of circuit design is useful for many engineers -- even those who may never actually design a circuit -- because it is likely that they will fabricate, test, or use these circuits in some way during their careers. This book provides a thorough and rigorous explanation of circuit design with a focus on the underlying principles of how different circuits work -- instead of relying completely on design procedures or "rules of thumb." In this way, readers develop the intuition that is essential to understanding and solving design problems in those instances where no procedure exists. Features a "Topical organization" rather than a sequential one -- emphasizing the models and types of analyses used so they are less confusing to readers. Discusses complex topics such as small-signal approximation, frequency response, feedback, and model selection. Most of the examples and exercises compare the analytical results with simulations -- Simulation files are available on the CD-ROM. A generic transistor is used to avoid repetition, presenting many of the basic principles that are common to FET and BJT circuits. Devotes a whole chapter to device physics